2019
DOI: 10.1073/pnas.1815412116
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost high-efficiency system for solar-driven conversion of CO 2 to hydrocarbons

Abstract: Conversion of carbon dioxide into hydrocarbons using solar energy is an attractive strategy for storing such a renewable source of energy into the form of chemical energy (a fuel). This can be achieved in a system coupling a photovoltaic (PV) cell to an electrochemical cell (EC) for CO2 reduction. To be beneficial and applicable, such a system should use low-cost and easily processable photovoltaic cells and display minimal energy losses associated with the catalysts at the anode and cathode and with the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 29 publications
2
99
0
2
Order By: Relevance
“…The achievement of stable, cheap and reproducible PSCs will be fundamental in view of their worldwide diffusion in the energy scenario, as well as integration with energy storage technologies. [38][39][40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…The achievement of stable, cheap and reproducible PSCs will be fundamental in view of their worldwide diffusion in the energy scenario, as well as integration with energy storage technologies. [38][39][40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…As one kind of promising next‐generation photovoltaic devices, perovskite solar cell (PVSCs) have drawn enormous research interest mostly due to their impressively high power conversion efficiency (PCE) . It is reported that perovskite materials have many superior optoelectronic properties, such as appropriate bandgap, long carrier life‐time, high optical absorption coefficient, and low exciton bind energy, which contribute a lot to device performance .…”
mentioning
confidence: 99%
“…Er zeigte eine Parallelität zwischen Photosynthese und bioinspirierten Katalysatoren, wies auf die Bedeutung und das Funktionsprinzip des Photosystems I (PSI) und II (PSII) hin und betonte dessen Relevanz für CO 2 ‐Abscheidestrategien. Seine Gruppe hat in einem seiner aktuellen Beiträge ein künstliches Photosynthesesystem auf Nicht‐Edelmetall‐Basis entwickelt und konnte CO 2 in Kohlenwasserstoffe mit einer außergewöhnlichen Solar‐Kohlenstoff‐Effizienz von 2.3 % umwandeln . Unter anderem beschrieb er die elektrochemische Reduktion von CO 2 am Fe‐haltigen Zn‐basierten zeolithischen Imidazolatgerüst (ZIF‐8) als Heterogenkatalysator .…”
Section: Sonntag 5 Maiunclassified